Assessment of the Utilization of Lipoprotein (a) and its Relationship with Cardiovascular Outcomes: A Retrospective Cohort Study from a Public Hospital in New York City - Maisha Maliha; Natalia Nazarenko; Sanjana Nagraj; Vikyath Satish; Amrin Kharawala; Pawel Borkowski; Vibhor Garg; Tinatin Saralidze; Dimitrios Karamanis; Leonidas Palaiodimos (Heart Views)
Introduction: Lipoprotein (a) [Lp(a)] is an independent genetic risk factor for atherosclerotic cardiovascular disease (ASCVD) and is associated with an increased risk of heart failure (HF), multiple vascular and valvular abnormalities and is closely linked to various lipid components, particularly low-density lipoprotein (LDL) cholesterol. Despite its clinical significance, Lp(a) testing has not gained widespread use in healthcare practice. Our study aimed to assess the utilization of Lp(a) testing and its association with ASCVD risk factors, HF phenotypes, vascular and valvular pathologies, lipid profiles, and the use of lipid-lowering drugs at a safety-net hospital within the largest municipal healthcare system in the United States. Methods: We conducted a retrospective study at Jacobi Medical Center, a public hospital in the Bronx, New York. Using a cutoff value of 75 nmol/L, we compared a study group with elevated Lp(a) levels to a control group. The primary outcomes assessed were the association between Lp(a) levels and ASCVD risk factors, HF phenotypes (classified by left ventricular ejection fraction), and vascular and valvular pathologies. Secondary outcomes included the relationship between elevated Lp(a) levels and lipid profiles, as well as the use of lipid-lowering medications such as statins, proprotein convertase subtilisin/kexin type 9 inhibitors, and ezetimibe. Results: The study included 78 patients (41.0% female, median age 52.0 years, interquartile range 44.0–66.0 years). Patients with elevated Lp(a) had a significantly higher incidence of HF with preserved ejection fraction (HFpEF) (18.8% vs. 0%, P = 0.004), but there was no significant association with HF with reduced ejection fraction (15.6% vs. 36.3%, P = 0.613) or HF with midrange ejection fraction (12.5% vs. 13.6%, P = 0.061). No significant associations were found between elevated Lp(a) and ASCVD risk factors, or valvular and vascular pathologies. However, patients with high Lp(a) levels had significantly higher LDL levels (96.5 mg/dL vs. 73.0 mg/dL, P = 0.04). There was no significant association between the use of lipid-lowering drugs and elevated Lp(a) levels. Notably, some patients exhibited unexpectedly high Lp(a) levels despite having a comparable demographic and comorbidity risk profile to those with normal Lp(a) levels. Conclusion: Patients with elevated Lp(a) levels were more likely to present with HFpEF and elevated LDL levels, although no significant associations were found with ASCVD risk factors, vascular, or valvular pathologies. The unexpectedly high Lp(a) levels in some individuals with similar risk profiles suggest the need for further research to refine guidelines for Lp(a) testing. Our study also highlighted the underutilization of Lp(a) testing in clinical practice, underscoring the importance of increasing awareness and improving ASCVD risk assessment strategies.